Somos todes youtubers? Indústria 4.0 e precarização do trabalho docente em tempos de pandemia - Gonçalves, Renata; Souza, Edvânia Ângela de [UNESP] (Cortez Editora Ltda, 2022)
Under the justification that they are necessary for social isolation and the preservation of public health, digital platforms in these times of the covid-19 pandemic have become part of the professional routine in various areas of work, including education. The information age of Industry 4.0 abruptly intensified into university life. We examine some of the disastrous impacts of Remote Emergency Education on Social Work teaching: which training for which society project? Are we all youtubers?

Sob a justificativa de que são necessárias ao isolamento social nem à preservação da saúde pública, as plataformas digitais nestes tempos de pandemia de covid-19 se tornaram parte do cotidiano profissional de diversas áreas do trabalho, incluindo a da educação. A era informacional da Indústria 4.0 se intensificou abruptamente à vida universitária. Examinamos alguns dos nefastos impactos do Ensino Emergencial Remoto para a docência em Serviço Social: que formação para qual projeto societário? Somos todes youtubers?
Are we all youtubers? Industry 4.0 and precariousness of teaching work in times of pandemic
Keywords: Covid-19; Industry 4.0; Digital platform; Emergency Remote Education; Social Work; Covid-19; Indústria 4.0; Plataforma digital; Ensino Remoto Emergencial; Serviço Social